Murder in midwinter - Hitchcock, Fleur (Nosy Crow, 2016)
Seated on the top of a bus, days before Christmas, Maya sees a couple arguing violently in the middle of a crowded Regent Street. They see her watching, she looks away, and the woman disappears. Maya goes to the police, who shrug and send her away. Then a body turns up. Now convinced she is a vital witness to a crime, the police send Maya into hiding in rural Wales but she resolves to get to the bottom of the mystery. Then the snow comes and no one can get out. But what if someone can still get in?
Keywords: Murder / Juvenile fiction; Witnesses / Juvenile fiction; Witnesses / Protection / Juvenile fiction; Children's stories; Wales / Juvenile fiction; Murder; Witnesses; Witnesses / Protection; Wales; Detective and mystery fiction; Fiction; Juvenile works; Children's fiction